2009
DOI: 10.1002/clc.20579
|View full text |Cite
|
Sign up to set email alerts
|

Value of Early Cardiac Troponin I to Predict Long‐Term Adverse Events After Coronary Artery Bypass Graft Surgery in Patients Presenting with Acute Coronary Syndromes

Abstract: Background High values of both preoperative and postoperative cardiac troponin I (cTnI) contribute to higher rates of short‐term cardiac events following coronary artery bypass graft (CABG) surgery in patients with acute coronary syndrome (ACS). The prognostic value of very early cTnI in this context is unclear. Hypothesis Measurement of cTnI very early after admission to the emergency room can be used as a prognosticator for long‐term outcomes after CABG. Methods We conducted a cohort study on 160 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The detection of myocardial injury is an important step in making the clinical decision to admit patients with chest pain to the coronary care unit. Studies evaluating the clinical value of cTnT were performed in patients with unstable angina pectoris 20,21 and patients who underwent coronary artery bypass grafting 22 or percutaneous coronary intervention. 23 These studies unequivocally demonstrated that elevated levels of cTnT are associated with poorer prognosis In patients without CAD, 41% had hs-cTnT values in the lowest quartile, compared with 12% in the multivessel group.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of myocardial injury is an important step in making the clinical decision to admit patients with chest pain to the coronary care unit. Studies evaluating the clinical value of cTnT were performed in patients with unstable angina pectoris 20,21 and patients who underwent coronary artery bypass grafting 22 or percutaneous coronary intervention. 23 These studies unequivocally demonstrated that elevated levels of cTnT are associated with poorer prognosis In patients without CAD, 41% had hs-cTnT values in the lowest quartile, compared with 12% in the multivessel group.…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 summarizes literature published since 20005,10-37 where investigators studied POC cardiac biomarker testing in emergency and disaster settings. Evidence-based results are varied, most probably because of lack of a uniformly systematic approach to the implementation and use of a variety of POC devices, as well as the heterogeneous test clusters employed in dissimilar environments.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of cardiac troponins in predicting the preoperative and postoperative mortality and morbidity have been demonstrated in various studies [9][10][11]. Filizcan et al [14] showed that cardiac troponin levels were one of the predictive factors for hospital mortality in AMI patients with ST-segment elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing patients with ACS and determining their treatment alternatives provide valuable information on the prognosis of these patients [9,10]. There are numerous studies which have shown an association between high preoperative and postoperative troponin levels associated with increased morbidity and mortality rates in patients undergoing CABG [11][12][13][14]. This raises the possibility that cardiac troponin levels may be used as a marker for the timing of CABG operations.…”
Section: Introductionmentioning
confidence: 99%